Building a Typology of Humor in Animated Comedies: Analysis of The Saudi Animated Comedy Masameer Classics - Alaboudi, Samah (International Journal of Language and Literary Studies, 2026)
The current study investigates the emergence of humor in the Saudi animated comedy Masameer Classics. The aim is to identify the humor techniques used to generate humor in the show. To do so, an amended typology made up of four categories (Language, Logic, Identity, and Action) and their 46 subsequent humor techniques was developed, based on two existing typologies in the literature. The coding of the data using the amended typology revealed that all four categories were used to generate humor in the show, with varying frequencies to their more specific techniques. Language dominated, followed by Identity, Logic, and Action. The prevalence of categories of humor that emerged in the animated comedy shed light on topics and themes highlighted in the show. The typology can be utilized in future research to identify how humor is generated in animated comedies, along with providing comedy creators with an insight into the specific techniques used to trigger humor in animated comedies.